2018
DOI: 10.1111/crj.12790
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound in diagnosis and follow up of community acquired pneumonia in infants younger than 1‐year old

Abstract: This study showed that LUS is superior to CXR in diagnosing infants with CAP who are younger than 1-year old. It also serves as a safe follow up tool and could support the decision of hospital discharge in this category of patients. Further studies with larger sample size and longer follow up duration are recommended to confirm the results of the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…Ianniello et al highlighted that LUS after 5 days showed a complete disappearance or decrease in size of subpleural pulmonary parenchymal lesions in 84.6% of their patients. Omran et al reported the complete regression or diminished size in 81.6% of patients on day 5 of treatment. We showed that children with noncomplicated CAP had an overall improvement already at T48 LUS control, while this trend was not described in children with complicated CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Ianniello et al highlighted that LUS after 5 days showed a complete disappearance or decrease in size of subpleural pulmonary parenchymal lesions in 84.6% of their patients. Omran et al reported the complete regression or diminished size in 81.6% of patients on day 5 of treatment. We showed that children with noncomplicated CAP had an overall improvement already at T48 LUS control, while this trend was not described in children with complicated CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the diagnosis of lung lesions in COVID-19, LUS can also diagnose and differentially diagnose the dyspnea caused by COVID-19 through BLUE and FALLS schemes [16][17][18]. Because LUS is non-radiative and repeatable, it can also be used to keep track of the patient's progress [19,20]. Coupled with the development and application of remote robotic ultrasound, such problems as lack of sonographers and backward equipment in the SARS-Cov-2 quarantine zone can be greatly alleviated.…”
Section: Discussionmentioning
confidence: 99%
“…After 5 days of treatment, the lung US showed a complete disappearance or a decrease in the size of consolidation patches in 84.6% of their patients, and 15% showed disease stability or an insubstantial decrease in size. Similarly, Omran et al described the complete regression or diminished size of the consolidations in 81.6% of patients on the fifth day of treatment, confirmed by the patients’ clinical improvement. The 7 infants (14.3%) who showed increased‐size consolidation patches had weaker clinical improvement and needed prolonged hospital stays.…”
Section: Discussionmentioning
confidence: 99%